Exosome-mediated delivery of siRNA molecules in cancer therapy: triumphs and challenges - Ubanako, Philemon; Mirza, Sheefa; Ruff, Paul; Penny, Clement (Frontiers in Molecular Biosciences, 2024)
The discovery of novel and innovative therapeutic strategies for cancer treatment and management remains a major global challenge. Exosomes are endogenous nanoscale extracellular vesicles that have garnered increasing attention as innovative vehicles for advanced drug delivery and targeted therapy. The attractive physicochemical and biological properties of exosomes, including increased permeability, biocompatibility, extended half-life in circulation, reduced toxicity and immunogenicity, and multiple functionalization strategies, have made them preferred drug delivery vehicles in cancer and other diseases. Small interfering RNAs (siRNAs) are remarkably able to target any known gene: an attribute harnessed to knock down cancer-associated genes as a viable strategy in cancer management. Extensive research on exosome-mediated delivery of siRNAs for targeting diverse types of cancer has yielded promising results for anticancer therapy, with some formulations progressing through clinical trials. This review catalogs recent advances in exosome-mediated siRNA delivery in several types of cancer, including the manifold benefits and minimal drawbacks of such innovative delivery systems. Additionally, we have highlighted the potential of plant-derived exosomes as innovative drug delivery systems for cancer treatment, offering numerous advantages such as biocompatibility, scalability, and reduced toxicity compared to traditional methods. These exosomes, with their unique characteristics and potential for effective siRNA delivery, represent a significant advancement in nanomedicine and cancer therapeutics. Further exploration of their manufacturing processes and biological mechanisms could significantly advance natural medicine and enhance the efficacy of exosome-based therapies.